Analysis of the performance of an extraction-condensation steam turbine on a cogeneration system of a Brazilian sugar-alcohol factory - Fiomari, Marcelo C.; Mashiba, Marcos H. S.; Junior, Ricardo A. R.; Takaki, Alessandro T.; Ramos, Ricardo A. V. (Natl Technical Univ Athens, 2006)
In this work a detailed thermodynamic analysis for an extraction-condensation steam turbine capable to drive a 40 MVA electricity generator in a sugar-alcohol factory was carried out. The use of this turbine in the cogeneration system showed that its efficiency contributed to increase the power generation, although the condensation reduces the overall efficiency of the plant. Sensibility analyses were performed to evaluate the behavior of the overall energy efficiency of a plant with the extraction-condensation turbine in function of the boiler efficiency, the specific consumption of steam in the processes and the condensation rate in the turbine. It was observed that the plant efficiency is very sensible to the condensation rate variation and it increases when there is an increase in the demand of steam for processes.
Keywords: cogeneration; extraction-condensation turbine; sugar cane industry; thermodynamic analysis